Analisis Sentimen Pariwisata di Kabupaten Malang dengan Menggunakan Metode BM25F, Neighbor Weighted K-Nearest Neighbor dan Seleksi Fitur Chi-Square - Pratitha Vidya Sakta; Indriati Indriati; Marji Marji (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
City Branding "The Heart of East Java" is one of the efforts used by the Malang District Tourism and Culture Office to market the region in the context of increasing regional tourism. Ratings and reviews relating to tourism in Malang Regency are numerous in the internet. One site to give ratings and reviews is on TripAdvisor. This study tries to analyze reviews from the public about Malang Regency tourism through sentiment analysis and is classified into two classes, positive and negative. In this study, sentiment analysis is carried out in several stages or processes. The process consists of preprocessing data, word weighting which is implemented using the BM25F algorithm, Neighbor Weighted K-Nearest Neighbor for document classification and Chi-Square for feature selection. K-Fold Cross Validation was tested (with K = 5) on the parameter ð‘˜ for the classification of NWKNN, bc, boost and k1 for BM25F. The test results show that the determination of stream weight values â€‹â€‹on BM25F sufficiently influences the results of the NWKNN classification. While the best final results for F-Measure, Accuracy, Precision, and Recall are produced at k = 30, chi-square ratio = 40%, constant (bc) = 0.5, boost head = 2, boost body = 5 and k1 = 1.9 as the best value for each parameter